The Impact of Promoter on Firm Value: Evidence from Emerging Economies - Aghila Sasidharan,; Rahul Sukumaran,; Sobhith Jose, (Asian Academy of Management Journal, 2024)
Using panel regression on a sample of 1,532 firms listed on the National Stock Exchange (NSE) of India and 450 firms in the Shanghai Stock Exchange (SSE) of China, this study examines the impact of promoter ownership on firm value. We find that promoter have positive impact on firm value in China while it is inversely related to India due to the entrenchment effect or opportunistic behaviour of the promoter. We provide evidence that the opportunistic behaviour of the promoter can be reduced only through monitoring by the corporate governance mechanisms such as board of directors. We contribute to the existing literature on corporate governance and corporate finance by examining the link between promoter ownership and firm value. Our results help the regulators and policy makers to formulate a regulation that reduces the opportunistic behaviour of promoters.